2009
DOI: 10.1002/prot.22383
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of chromosomal and exogenous dihydrofolate reductase from Staphylococcus aureus in complex with the potent inhibitor trimethoprim

Abstract: Dihydrofolate reductase (DHFR) is the enzyme responsible for the NADPH-dependent reduction of 5,6-dihydrofolate to 5,6,7,8-tetrahydrofolate, an essential cofactor in the synthesis of purines, thymidylate, methionine, and other key metabolites. Because of its importance in multiple cellular functions, DHFR has been the subject of much research targeting the enzyme with anticancer, antibacterial, and antimicrobial agents. Clinically used compounds targeting DHFR include methotrexate for the treatment of cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 26 publications
2
104
0
Order By: Relevance
“…However, while this structure of Sa(F98Y):ÎČ-NADPH:TMP may be thermodynamically stable in the crystal, there is little evidence that it is kinetically stable in solution, as shown by isothermal calorimetry experiments revealing attenuated binding with or without NADPH 7 and dissociation experiments shown here that reveal a very fast dissolution of the complex between Sa(F98Y) and TMP. Although studies on the catalytic cycle of DHFR have described a classical binding order where NADPH binds prior to DHF 33 , various solution experiments (**ref Heaslet and Polshakov) have shown that the binding of TMP and NADPH can occur in any order, ultimately leading to a stable ternary complex.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, while this structure of Sa(F98Y):ÎČ-NADPH:TMP may be thermodynamically stable in the crystal, there is little evidence that it is kinetically stable in solution, as shown by isothermal calorimetry experiments revealing attenuated binding with or without NADPH 7 and dissociation experiments shown here that reveal a very fast dissolution of the complex between Sa(F98Y) and TMP. Although studies on the catalytic cycle of DHFR have described a classical binding order where NADPH binds prior to DHF 33 , various solution experiments (**ref Heaslet and Polshakov) have shown that the binding of TMP and NADPH can occur in any order, ultimately leading to a stable ternary complex.…”
Section: Discussionmentioning
confidence: 70%
“…3–6 The F98Y point mutation in DHFR is the pivotal mutation clinically observed to confer high levels of resistance to trimethoprim, 5 primarily resulting in a change in entropy of ligand binding and a loss of synergy, or binding affinity, between the inhibitor and NADPH cofactor. 7 New generations of antifolates that effectively target the mutated forms of DHFR will be critical for prolonging the utility of this class of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Linkers can be added to the para position of the trimethoxyphenyl ring of TMP without interfering with DHFR binding 16 . By contrast, the 2,4-diaminopyrimidine ring of TMP is buried in the DHFR substrate pocket 21 , so we predicted that adding a bulky photocage to this group would effectively block DHFR binding. Neither photocaged TMP nor a photocaged modular chemical inducer of dimerization have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…A crystal structure of S1 with TMP revealed six molecules in the asymmetric unit, only three of which were the ternary structure. The other three S1 proteins bound only TMP, indicating the altered interactions of the S1 enzyme with NADPH (Heaslet et al 2009). …”
Section: Resistance To Trimethoprimmentioning
confidence: 99%
“…4A). Interestingly, this residue is an isoleucine in S1 DHFR, which is known to contribute to TMP resistance (Heaslet et al 2009). In the Gram-negative enzymes, Phe at position 31 is balanced by less bulky residues on the opposite side of the active site (Fig.…”
Section: Resistance To Trimethoprimmentioning
confidence: 99%